Tests of a Signaling Hypothesis: The Choice between Fixed- and Adjustable-Rate Debt - Guedes, Jose; Thompson, Rex (Review of Financial Studies, 1995)
We develop a model wherein the choice between adjustable- and fixed-rate debt can serve as a signal of firm quality. The nature of the signal depends on expected inflation volatility relative to other risk parameters. Evidence from a matched sample of debt announcements over the period 1978 to 1986 shows a difference of - 2.05 \ \ rm percent between stock price reactions to adjustable rate and fixed rate announcements when expected inflation volatility is above an estimated threshold. Below this threshold, the difference is +0.98 \ \ rm percent. The evidence supports the hypothesis that the riskier debt choice serves as a favorable signal of firm quality.